Virtual reality-based sensorimotor adaptation shapes subsequent spontaneous and naturalistic stimulus-driven brain activity. (26th October 2022) - Wilf, Meytal; Dupuis, Celine; Nardo, Davide; Huber, Diana; Sander, Sibilla; Al-Kaar, Joud; Haroud, Meriem; Perrin, Henri; Fornari, Eleonora; Crottaz-Herbette, Sonia; Serino, Andrea
Abstract: Our everyday life summons numerous novel sensorimotor experiences, to which our brain needs to adapt in order to function properly. However, tracking plasticity of naturalistic behavior and associated brain modulations is challenging. Here, we tackled this question implementing a prism adaptation-like training in virtual reality (VRPA) in combination with functional neuroimaging. Three groups of healthy participants ( N  = 45) underwent VRPA (with a shift either to the left/right side, or with no shift), and performed functional magnetic resonance imaging (fMRI) sessions before and after training. To capture modulations in free-flowing, task-free brain activity, the fMRI sessions included resting-state and free-viewing of naturalistic videos. We found significant decreases in spontaneous functional connectivity between attentional and default mode (DMN)/fronto-parietal networks, only for the adaptation groups, more pronouncedly in the hemisphere contralateral to the induced shift. In addition, VRPA was found to bias visual responses to naturalistic videos: Following rightward adaptation, we found upregulation of visual response in an area in the parieto-occipital sulcus (POS) only in the right hemisphere. Notably, the extent of POS upregulation correlated with the size of the VRPA-induced after-effect measured in behavioral tests. This study demonstrates that a brief VRPA exposure can change large-scale cortical connectivity and correspondingly bias visual responses to naturalistic sensory inputs.